العلاقة بين مفهوم الذات والمهارات الحياتية لدى ضعاف السمع - شولح، عبير محمد عبدالعزيز (جامعة عين شمس - كلية البنات للآداب والعلوم والتربية, 2020)
هدفت الدراسة إلى التعرف على العلاقة بين مفهوم الذات والمهارات الحياتية لدى ضعاف السمع، التعرف على الفروق في مستوى مفهوم الذات تعزى لمتغير النوع (ذكر / أنثى)، التعرف على الفروق في مستوى المهارات الحياتية تعزى لمتغير النوع (ذكر / أنثى)، التعرف على الفروق في مستوى مفهوم الذات ترجع للمرحلة العمرية (١٠-١٢)، و (13-15) سنة، التعرف على الفروق في مستوى المهارات الحياتية ترجع للمرحلة العمرية (10-12)، و (13-15) سنة، ولتحقيق ذلك استخدمت الباحثة المنهج الوصفي التحليلي، حيث بمقتضاه تم وصف للمعطيات المدروسة وتحليلها، أي وصف العلاقة بين مفهوم الذات والمهارات الحياتية لدى ضعاف السمع، تكون مجتمع الدراسة من الطلاب والطالبات ضعاف السمع ممن تتراوح أعمارهم ما بين (11-15) عام، من مدرسة التربية الأمل بمحافظة كفر الشيخ، وتم اختيار عينة تكونت من (25) طلاب، (25) طالبات، وتمثلت أدوات الدراسة في كل من مقياس مفهوم الذات (إعداد الباحثة)، مقياس المهارات الحياتية (إعداد الباحثة)، أظهرت نتائج الدراسة وجود علاقة ارتباطية موجبة دالة إحصائيا بين مفهوم الذات والمهارات الحياتية، ووجود فروق بين الذكور والإناث في مفهوم الذات والمهارات الحياتية لصالح الإناث، ووجود فروق في مفهوم الذات والمهارات الحياتية لصالح عمر (10-12) عام.
The study aimed to identify the relationship between self-concept and life skills of the hearing impaired, the differences in the level of self-concept due to the gender variable (male / female), the differences in the level of life skills attributed to the gender variable (male / female), the differences At the level of self-concept it refers to the age stage (10-12) and (13-15) years, and the differences in the level of life skills due to the age stage (10-12) and (13-15) years. To achieve this, the researcher used the method Descriptive and analytical, whereby the studied data were described and analyzed, The study sample consisted of hearing impaired students, age between (11-15) years, from the Al Amal School in Kafr El-Sheikh, and a sample consisting of (25) male and (25) female students, and the study tools were represented in each scale Self-concept (the researcher's preparation), life skills scale (the researcher's preparation), the results of the study showed the existence of a positive statistically significant correlation between self-concept and life skills, the existence of differences between males and females in self-concept and life skills for females, and the existence of differences in self-concept and life skills For age (10-12) years old.
Keywords: الصحة النفسية -- المهارات الحياتية -- الذات -- الطلاب ضعاف السمع